Genetic characterisation of the Nero d’Aspromonte pig population in Southern Italy - Ervin Shishmani; Valentino Palombo; Giuseppina Schiavo; Siria Tavaniello; Mengjun Wu; Marisa Palazzo; Giuseppe Maiorano; Luca Fontanesi; Mariasilvia D’Andrea (Italian Journal of Animal Science)
The aim of this study was to investigate the genomic diversity of the Nero d’Aspromonte (NA) pig population. NA is a subpopulation derived from the Apulo Calabrese (AC) breed that has been reared in total isolation within the Polsi area of Aspromonte, Calabria, Italy. NA is traditionally recognised and used by local farmers for the production of typical products. The growing interest in this subpopulation has led local farmers to create a cooperative to promote NA pig meat and help preserve the cultural heritage associated with this local population. A total of 40 NA pigs were included in our study and genotyped with the Illumina GGP Porcine array. Admixture, TreeMix, and run of homozygosity (ROH) analyses were performed to investigate genetic diversity within the NA subpopulation and its relationship with the AC breed and other Italian pig breeds. The NA population clearly originated from the AC breed. The lower inbreeding and average ROH size in NA compared to AC may indicate that NA differentiated from the original AC genetic pool with the contribution of admixture from other genetic backgrounds in addition to the effects of genetic isolation and genetic drift. The analysis of the genetic diversity of the NA subpopulation showcases the utility of genomic analyses to reconstruct the genetic history of local populations. A specific conservation program for this genetic resource may further support the sustainable development of local pig production systems based on traditional farming practices as a part of agricultural cultural heritage.